The Effectiveness of Pastoral Visits for the Spiritual Growth of Adolescents at GMIT Mawar Saron Liliba Klasis East Kupang City - Riwu*, Mari Magdalena Ide; Leobisa, Jonathan; Kase, Simon (Universitas Syiah Kuala, 2024)
The study seeks to evaluate the efficacy of spiritual visits in facilitating the spiritual growth of teenagers. The employed methodologies encompass quantitative approaches such as surveys and questionnaire research, as well as qualitative methods involving in-depth interviews with teenagers, parents, and church leaders. The assessment of spiritual development might be based on enhanced comprehension of religious doctrines, advancement in the practice of prayer, active engagement in church-related endeavors, favorable modifications in conduct, and enhanced mental and emotional well-being. The study's findings indicate that the inclusion of a priest has a significant and beneficial influence on the spiritual growth of adolescents. The success of pastoral visits is supported by factors such as the frequency of visits, the quality of the pastor-teenager relationship, and a personalized approach. However, there are also hindrances such as time constraints and ineffective communication. The findings of this study recommend increasing the number of visits, offering specialized training to priests, adopting a more personalized approach, engaging families, and leveraging technology to enhance the effectiveness of pastoral visits. By employing this approach, it is anticipated that pastoral visits will provide greater efficacy in directing young individuals towards enhanced spiritual maturation.